Effect of Cr2O3 on the bandgap of TiO2 thin films - Брус, Віктор Васильович; Мостовий, Андрій Ігорович; Мар’янчук, Павло Дмитрович (Eastern-European Journal of Enterprise Technologies, 2013)
Titanium dioxide (TiO2) is a large band gap semiconductor with many interesting properties. This material possesses high refractive index and low absorption coefficient in visible range, which makes it an excellent optical coating material. Cr2O3 seems to be one of the most promising impurities in TiO2 as it shifts the optical absorption spectrum towards the visible range and improves the photocurrent density of TiO2. Titanium dioxide thin films doped with chromium oxide (Cr2O3 – 1; 3; mol%) were deposited onto glass substrates in a universal coating system Leybold – Heraeus L560 by electron-beam evaporation. The transmission spectra of the TiO2 and TiO2 - Cr2O3 thin films were measured by a spectrophotometer SF-2000 within the wavelength range 200 - 1100 nm with a step of 1 nm. The effect of Cr2O3 concentration on the band gap of titanium dioxide thin films was investigated.